Tidying up a few misconceptions around evidence-based policing: Reply to Staller and Koerner (2021) - Koziarski, Jacek (International journal of comparative and applied criminal justice, 2021)
In this piece we reply to a commentary from Staller and Koerner on our work entitled, #Defund or #Re-Fund? Re-Examining Bayley’s Blueprint for Police Reform. In short, we agree on the necessity of reflexivity within policing research and the area of evidence-based policing more specifically, but also see this reply as an opportunity to clarify some misconceptions around evidence-based policing and what it means to be “evidence-based.” More specifically, we touch upon the flexibility of evidence-based policing to be implemented in tandem with other reform approaches, the value of experiential knowledge and qualitative methods within evidence-based policing, and the confounding of evidence and evidence-based. We conclude on the point of reflexivity and put out a call for follow-up studies that examine the implications of evaluated police practices.